2018
DOI: 10.1103/physrevb.98.205130
|View full text |Cite
|
Sign up to set email alerts
|

Ferromagnetically correlated clusters in semimetallic Ru2NbAl Heusler alloy and its thermoelectric properties

Abstract: In this work, we report the structural, magnetic and electrical and thermal transport properties of the Heusler-type alloy Ru 2 NbAl. From the detailed analysis of magnetization data, we infer the presence of superparamagnetically interacting clusters with a Pauli paramagnetic background, while short-range ferromagnetic interaction is developed among the clusters below 5 K. The presence of this ferromagnetic interaction is confirmed through heat capacity measurements. The relatively small value of electronic c… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
24
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(31 citation statements)
references
References 80 publications
7
24
0
Order By: Relevance
“…This upturn diminishes systematically with increasing Cr concentration in the series. As also demonstrated in Fe 2 VAl 17 and NbAl 18 Heuslers, such an upturn is mainly associated with the presence of magnetic clusters. Generally, the magnetic clusters present in any system rest at lowest energy at low temperature.…”
Section: Resultssupporting
confidence: 53%
See 1 more Smart Citation
“…This upturn diminishes systematically with increasing Cr concentration in the series. As also demonstrated in Fe 2 VAl 17 and NbAl 18 Heuslers, such an upturn is mainly associated with the presence of magnetic clusters. Generally, the magnetic clusters present in any system rest at lowest energy at low temperature.…”
Section: Resultssupporting
confidence: 53%
“…The additional terms, 2 , accommodates the magnetic cluster formation with the quantity N being the number of clusters present in the system. The term includes the extended temperature range beyond /50 as , the Debye temperature, has not been separately determined for these compositions 18 . The experimental data fit nicely to this equation in the temperature range (2–25) K, as shown in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Figure 10(b) shows the temperature dependence of zT for Co 2 MnSi calculated using the PF value (Figure 5(b)) and the κ tot value (Figure10(a)). Due to the high κ tot , the maximum zT value, zT max ,ofCo 2 MnSi is 0.039, which is obtained at temperatures above 900 K. Although this zT max value is far below the standard level of zT = 1, it is higher than that of Co 2 TiSn (0.033 at 370-400 K)[38] and those of semi-metallic full-Heusler compounds (0.0052 at 300 K for Ru 2 NbAl[28] and 0.0027 at 300 K for Ru 2 VAl 0.25 Ga 0.75[29]). It should be noted that the κ tot of Co 2 MnSi is not equal to the carrier thermal conductivity, κ e .…”
mentioning
confidence: 90%
“…Since then, many studies have been dedicated to investigate the electronic and magnetic properties of ternary and quaternary full-Heusler compounds. It has been revealed that full-Heusler compounds exhibit a variety of electronic properties; they exhibit the properties of semiconductors [9][10][11][12][13][14][15][16][17][18], spingapless semiconductors (SGSs) [19][20][21][22][23][24][25][26], semimetals [27][28][29], metals [30][31][32][33][34] and half-metals (HMs) [32,. Considering the magnetic properties, they have been reported to exhibit nonmagnetism [9][10][11][14][15][16][17][18], ferromagnetism [12, 19-24, 30-33, 36-46, 48-58, 61-66, 68-78], ferrimagnetism [13,30,35,47,59,60,67] and antiferromagnetism [25,26,34].…”
Section: Crystal Structures and Magnetic Properties Of Full-heusler Cmentioning
confidence: 99%
“…The HAs are remarkable due to their active role in the spin‐injection devices, 13‐17 spintronic devices and high thermoelectric performance, 18‐20 tunnelling magneto‐resistance, 21‐24 spin filters, 16 giant magneto resistance, 25,26 magnetic sensors, 27 non‐volatile magnetic random access memories, 28,29 electro‐mechanical applications 30 . The extensive theoretical 31‐35 and experimental 36‐40 studies of the HAs have been reported in the literature in context to the thermoelectric applications due to their high power factor and low thermal conductivities.…”
Section: Introductionmentioning
confidence: 99%